Hong Kong’s Tightened Film Censorship and Its Implication on Hong Kong Cinema - Heng, Siu (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
Hong Kong’s film censorship had become completely apolitical on the eve of the city’s change of sovereignty from Britain to China in 1997. This paper will review film censorship practices in the early handover period, drawing from the first-hand experience of the author, who was a public officer working in the film censorship institution. It will examine how film censorship practices in Hong Kong have changed to reintroduce political censorship following the Chinese government’s tightened grip over this former British colony, such as imposing the National Security Law (NSL) prompted by a massive civic movement in 2019. Political censorship has begun to manifest in a more covert manner within the film industry. Filmmakers, distributors, and screening organisers are finding ways to navigate the tightened censorship, ranging from circulating works overseas to incorporating acts of censorship as part of the creative process. The dynamics between the state’s control, the industry’s collaboration, and the filmmakers’ reactions are collectively shaping the evolving landscape of Hong Kong cinema under a mutating political environment in the post-NSL Hong Kong.